A DESIGN OF COMPUTER NETWORK REPORT MONITORING SYSTEM BASED OPEN SOURCE USING CACTI AT BANDA ACEH - Patra, Mohd. Iqbal; Fathiah, Fathiah (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2015)
Cacti as an open source application is a network monitoring system based on protocol SNMP (Simple Network Management Protocol) which allows the network manager to monitor the network traffic of each device. This application uses Linux operating system, MySQL database, SNMP module, and also additional plug-in Cereus Reporting on Cacti graphs for easy printing monitoring report. System testing was conducted on the engine performance monitoring network traffic in the process of monitoring network devices. This study results an implementation of network monitoring system using Linux-based Cacti applications and SNMP that can work well according to the design made. The results of the implementation of this application demonstrates the usage of network bandwidth used and facilitate the monitoring graph report that can be used in evaluating the internet services performance in the office of Population and Civil Registration Banda Aceh.Â Keywords: Network Monitoring Systems, Cacti, SNMP, Network Traffic, report